Clinicopathologic Relevance of Claudin 18.2 Expression in Gastric Cancer: A Meta-Analysis - Ungureanu, Bogdan Silviu; Lungulescu, Cristian-Virgil; Pirici, Daniel; Turcu-Stiolica, Adina; Gheonea, Dan Ionut; Sacerdotianu, Victor Mihai; Liliac, Ilona Mihaela; Moraru, Emil; Bende, Felix; Saftoiu, Adrian (Frontiers in Oncology, 2021)
An increasing number of tumor markers have been discovered to have potential efficacy as diagnostic and prognostic tools in gastric cancer. We aimed to assess putative correlations between Claudin 18.2 expression and pathological or prognosis features in patients with gastric cancer. MEDLINE, Web of Science, EBSCO, and ClinicalTrials.gov were used to search for relevant studies from their inception to 30 October 2020. Finally, a total of 6 articles were included in this meta-analysis. Review Manager 5 software was applied to examine the heterogeneity among the studies and to calculate the odds ratio with 95% CI by selecting corresponding models, in evaluating the strength of the relationship. Publication bias test was also conducted. No bias and no significant correlations were found between CLDN 18.2 and TNM stages, Lauren classification, HER2, grading or overall survival. This meta-analysis expounded that the relationship with CLDN 18.2 and pathological features depends on the percentage of staining of tumor cells for which CLDN 18.2 is considered positive. Our pooled outcomes suggest that targeted therapy for CLDN 18.2 could be effective if certain criteria will be established.